Developing an Interactive Learning Medium for A1-Level Reading Comprehension on 'Zeit mit Freunden' Using the Baamboozle Application (International Journal of Education and Literature, 2025)
The objective of this research is to develop interactive learning media using the Baamboozle application with the topic “Zeit mit Freunden” on reading skill level A1. The present study was conducted in the language laboratory of the Faculty of Language and Arts, State University of Medan. The present research employs the developmental model of Richey and Klein, which comprises three distinct stages: (1) planning, (2) making, and (3) evaluation. The data presented herein were collected through a combination of interviews, observations, and a thorough literature study, with the material drawn from the publication entitled Netzwerk neu A1. The result of this research is a digital game-based interactive learning media designed to improve students reading ability at A1 level. The aspects that are assessed include content, interactivity, ease of use, and design. The validation process was conducted by media and material experts, and the result was 92, which is classified as very good.